GAMBARAN KEPUASAN PASIEN DI POLIKLINIK SORE RSUD X KABUPATEN SEMARANG - Irianti, Gita Febri; Jati, Sutopo Patria; Purnami, Cahya Tri (LPPM Universitas Awal Bros, 2025)
Patient satisfaction is an essential indicator in assessing the quality of health services, especially in outpatient services at afternoon clinics designed to meet community needs. This study aims to describe the level of patient satisfaction with the services of the Afternoon Clinic at X Regional General Hospital in Semarang Regency, using the HEALTQUAL service quality dimensions. The study used a cross-sectional, quantitative design with 227 respondents selected by proportional sampling from a total population of 1,315 patients during the period January–June 2025. Data were collected through a questionnaire that had been tested for validity and reliability and then analysed descriptively using SPSS. The results showed that the communication dimension received 75.8% strongly agree, the physical evidence 79.3% strongly agree, the efficiency 62.6%–67.8% strongly agree, and the safety 60.8%–70.9% strongly agree. In contrast, the empathy dimension was dominated by strongly agree and agree responses. The conclusion of this study indicates that the services provided by the Afternoon Polyclinic at X Regional General Hospital in Semarang Regency have met the expectations of the majority of patients. It is recommended that the hospital conduct continuous evaluations, particularly in terms of physical facilities and optimisation of technology-based service systems, to maintain and improve patient satisfaction.